A Comparative Study of Curve of Spee and Arch Circumference Between Class I Nor-mal Occlusion and Class II Division 1 Ma-locclusion - Huda A Al-Sarraf; Ne'am F Agha; Alaa' D Al-Dawoody (University of Mosul, College of Dentistry, 2010)
Aims: The purpose of this study was to determine the curve of Spee in class I and class II division 1 malocclusion groups to investigate whether there is a relationship between the depth of Curve of Spee with arch circumference and other variables (overjet and overbite) between two classes of occlusion. Materials and Methods: 60 dental casts of untreated adolescents, 30 girls and 30 boys aged 12-15 years, were obtained from secondary schools at Mosul City. The sample included 2 groups; the class I occlusion group and class II1 malocclusion group, each group comprised from 30 subjects (15 boys and 15 girls). The depth of curve of Spee and arch circumference were measured on mandibular dental casts. Overjet and overbite were assessed with a vernia. Description of the variables within each class and comparison of the variable between two classes were assessed by student t-test. In addition, a correla-tion coefficients between the depth of curve of Spee and other variables were calculated. Results: the results showed that there were no significant differences between genders within the groups for all va-riables. However, these variables showed sexual differences between two groups. Statistically signifi-cant correlation was also found between the depth of Spee and overbite, overjet and arch circumferences in both groups.